Grain morphology and strength dilatancy of sands. Issue 4 (30th April 2019) - Guida, G.; Sebastiani, D.; Casini, F.; Miliziano, S.
Abstract : The presented experimental study, from micro to macro scale, assesses the effects of grain shape on the strength-dilatancy behaviour and physical properties of seven natural sands of different origins and mineralogical composition. The micro-scale has been characterised by processing two-dimensional image of grains, using the fractal analysis of particle contour to define their shape. The macroscopic material properties are evaluated performing direct shear tests at three different normal stresses, and measuring void ratios limit and angles of repose. An innovative method to interpret the experimental data obtained has pinpointed interesting relationships linking the morphological features of grains to the mechanical and physical properties of sands. Data confirm that the increase in grain shape irregularity produces an increase in all the variables investigated: void ratios limit, friction angles and dilatancy parameters.